2019
DOI: 10.1007/s10461-019-02759-3
|View full text |Cite
|
Sign up to set email alerts
|

Personal Approach to Treatment Choices for HIV (PATCH): Randomized Controlled Trial of a Brief Motivational Enhancement Intervention to Improve Medication Adherence in Persons with HIV

Abstract: This pilot randomized controlled trial evaluated the feasibility and efficacy of a brief motivational enhancement intervention to improve adherence to antiretroviral therapy in persons with HIV called Personal Approach to Treatment Choices for HIV (PATCH). We compared PATCH to an active control condition on self-reported adherence, clinical outcomes, and psychosocial outcomes. Participants were 34 individuals (61.8% male, M age = 47.1) receiving HIV-related services who were suboptimally engaged in care. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Some researchers have found that, while MI leads to subjective improvements in quality of life and reduction in some risk behaviors, this has not necessarily translated into changes in objective measures of adherence or VS (26)(27)(28). Furthermore, consistent with the SCM's experience, there is extensive literature on the difficulty of learning MI (29).…”
Section: Intervention Challenges From the Scm Perspectivementioning
confidence: 99%
“…Some researchers have found that, while MI leads to subjective improvements in quality of life and reduction in some risk behaviors, this has not necessarily translated into changes in objective measures of adherence or VS (26)(27)(28). Furthermore, consistent with the SCM's experience, there is extensive literature on the difficulty of learning MI (29).…”
Section: Intervention Challenges From the Scm Perspectivementioning
confidence: 99%